China versus the west : the global power shift of the 21st century - Tselichtchev, Ivan. (Singapore : Wiley, 2012)
China Versus the West is an innovative book. The author, a leading specialist on the international and Asian economy and business, presents the most comprehensive picture of the changing power balance between the emerging superpower China and the "old" developed economies of the West: mainly the US, Europe and Japan. The reader can clearly see in what areas and to what extent China has become the world leader, in what areas it is catching up and in what areas the West retains its superiority and has a chance to strengthen it further. At the same time, I. Tselichtchev unveils a breath-taking story of the global economy and business in the brave new world which is non-"West-led" and where major growth dynamics are coming from large emerging economies. A radically changing economic environment requires new government policies and business strategies. The book contains many valuable suggestions and ideas. Using his own analytical framework, the author presents a set of options and alternatives for Western businesses in the wake of China's production and export offensive. The book provides a uniquely sharp and thought-provoking analysis of the factors behind the global crisis of 2008-2009, largely different from what we see in other publications, and examines its implications for the global power balance. I. Tselichtchev vividly shows that it was not global, but Western crisis of a structural character which drastically changed the China-West power balance in the former's favor. He provides strong arguments showing that today's China is structurally and macro-economically stronger than most countries of the West. This leads him to rethinking the very essence of the Chinese model of capitalism and to its new definition. He expresses unconventional, sometimes controversial, but well-founded views about China's problems and weaknesses and the prospects for its political evolution.
The book ends with invaluable insights into China's unique role in the world economic history, the essence of the non-"West-led" multipolar world and the positions of its major players. Arguing that from now on no single country will be ever able to "rule the world", it shows new opportunities dynamic China is opening for the West. Thoroughly analyzing and discussing a wide range of the key, often complicated issues which are now in the focus of the world's attention, the book remains very reader-friendly. It is written in the form of an unconstrained dialogue with the reader, containing a lot of the author's on-the-spot impressions, interesting facts, remarks and quotations. China Versus the West is a must reading for everyone who wants to know more about the global developments, China and the West, and also, perhaps, to get valuable inputs and hints to find his or her own place in today's new world. It is highly recommended for policy-makers, business people, academics, analysts and journalists. It is a valuable source for professors and students of the universities and business schools.
Includes bibliographical references and index.
Keywords: International economic relations; Produktionens internationalisering; Kina; Economic history; International economic relations; China -- Economic conditions; China; Electronic books; Electronic books